Interdisciplinaridade e serviço social: um estudo do exercício profissional no NUDE, campus São Borja - (:unkn) unknown (Universidade Federal do Pampa, 2014)
The present Work of Course Completion in Social Service has as title "Interdisciplinarity and Social Service: a study of professional exercise in NuDe, Campus São Borja". The main objective is to analyze the particularity of the interdisciplinary work of the Social Worker in the multiprofessional team of the NuDe, with the purpose of offering subsidies that contribute to the professional intervention in space socio-occupational. The methodology used refers to bibliographic research and material on intervention project carried out with users of the NuDE, that have interconnection with the student assistance policy the UNIPAMPA, with which it was obtained grant to seek answers to the research problem. In this regard, the object meant unveil what is special about the Social Service on interdisciplinary work performed with the multiprofessional team. The theme is relevant to the Social Service mainly to that refers to the work process and its impact along the multiprofessional team and users of the policy of student assistance. The present study is based on theoretical composition the following categories: Work Process, Social Service, Education and Interdisciplinarity. In this sense, uncover how perspective interdisciplinary work implies the possibility to interact with other areas of activity and respect them by ensuring its particularities and knowledges.
Keywords: Serviço Social; Prática profissional; Estudantes - Programas de assistência; Unipampa; Social Service; Professional Practice; CNPQ::CIENCIAS SOCIAIS APLICADAS